n-3 PUFA-supplemented perioperative immunonutrition on postoperative outcomes in gastric cancer: a systematic review and meta-analysis - Yang, Fan; Zhou, Bei; Yang, Lebin; Wei, Zheng; Liang, Yi; Wang, Xuan; Shan, Hanguo (Frontiers in Nutrition, 2026)
ObjectiveTo evaluate the impact of perioperative immunonutritional regimens that included n-3 polyunsaturated fatty acids (n-3 PUFAs)—ranging from n-3 PUFA monotherapy to complex formulas combined with other immunonutrients—on postoperative outcomes in gastric cancer patients.BackgroundAlthough preventing postoperative complications is crucial for gastric cancer patients, consensus is lacking on the efficacy and optimal timing of administration of perioperative immunonutrition supplemented with n-3 PUFAs.MethodsWe systematically searched PubMed, Embase, Web of Science, and the Cochrane Library for randomized controlled trials (RCTs) evaluating perioperative immunonutrition with n-3 PUFAs in gastric cancer surgery patients. Manual searches of reference lists were also conducted. The primary endpoint was total postoperative complications. Secondary endpoints included immune function [CD4+ T lymphocytes (CD4+ cells), CD8+ T lymphocytes (CD8+ cells), CD4+/CD8+ ratio, total lymphocytes, immunoglobulins IgA, IgG, IgM], nutritional status (transferrin, albumin, prealbumin), inflammatory markers (IL-6, TNF-α, CRP), and recovery indices (time to first flatus, length of hospital stay). Data were analyzed using RevMan v5.3 with a random-effect model.ResultsSixteen RCTs involving 1,642 patients were included. The meta-analysis demonstrated that perioperative n-3 PUFA supplementation significantly reduced the overall incidence of postoperative complications and promoted earlier recovery, as evidenced by a shortened time to first flatus and a reduced length of hospital stay. Furthermore, the n-3 PUFA group showed significant improvements in immunological (CD4+ T cell (%), CD4+/CD8+ ratio, total lymphocytes, IgA, IgG), inflammatory (IL-6, TNF-α, CRP), and nutritional (prealbumin) parameters. However, no significant differences were observed in CD8+ T cell (%), IgM, transferrin, or albumin levels between groups.ConclusionThe perioperative application of immunonutrition containing n-3 PUFAs can reduce the incidence of postoperative complications in patients with gastric cancer, improve immune function and nutritional status, mitigate inflammatory responses, and promote early postoperative recovery.